Endophytic Bacteria Bengkulu's Coffee and Their Prospects - Dadan Supardan; Yosi Yulizah; Fatkhanuddin Aziz; Fauziah Fitriana (Biota, 2023)
Antimicrobial resistance (A.M.R.) is one of the main threats in the health sector. Most antimicrobials, including antibiotics, antifungals, antivirals, and antiparasitics, are derived from bioactive compounds found in bacteria, particularly the actinomycetes group. This study aimed to isolate and test endophytic bacteria on coffee plants against antibiotic-resistant pathogenic bacteria, namely penicillin-resistant S. aureus. This study used several methods: endophytic bacteria isolation, bacterial purification, gram staining, and endophytic bacteria antagonist test against antibiotic-resistant bacteria. Eight endophytic coffee isolates were obtained from the roots and pods of Robusta coffee. One bacterial isolate with the code AR4 had an antagonistic effect on tetracycline-resistant S. aureus bacteria.